Treatments applied to children’s sexual offenders (Legal journal - Research in Legal and Social Sciences, 2018)
This paper describes treatments and measures that can be applied to convicts of child sex abuse. It includes a detailed study, from a general perspective withregard to the measures adopted by other countries. Firstly, the characteristics of child molesters are broadly described, based on scientific-criminologicalfoundations. After that, it follows a description of some instruments of the most relevant psychological diagnosis, as well as the treatments that are applied to child molesters in different parts of the world, such as: psychological treatment, chemical castration and physical castration. The research also makes reference to the Penal Enforcement Code`s inconvinient, regarding criminal records, and it proposes the creation of a sex offender registry. Finally, and after an analysis of paraguayan law, this investigation concludes with the need to set, besides the penalties, programmes that imply a penitentiary treatment during conviction, and a surveillance of sex offenders -after they have served in prison- that enables an effective prevention ofrecurrence in this felony offense.
Keywords: criminal law; pedophilia; ex abuse; children; castration